2012
DOI: 10.1128/jb.00045-12
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids Regulate Stress Resistance and Virulence Factor Production for Listeria monocytogenes

Abstract: dFatty acids (FAs) are the major structural component of cellular membranes, which provide a physical and chemical barrier that insulates intracellular reactions from environmental fluctuations. The native composition of membrane FAs establishes the topological and chemical parameters for membrane-associated functions and is therefore modulated diligently by microorganisms especially in response to environmental stresses. However, the consequences of altered FA composition during host-pathogen interactions are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 64 publications
5
84
1
Order By: Relevance
“…1b supplemental) that were identified as anteiso C15:0 (52.3%) and anteiso C17:0 (40.8%). The results are in perfect accord with previous studies on strain cld-2 [2, 5, 12]. Growth in the presence of 2-MP led to two novel major peaks in the chromatograph with retention times of 2.61 and 3.24 min (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…1b supplemental) that were identified as anteiso C15:0 (52.3%) and anteiso C17:0 (40.8%). The results are in perfect accord with previous studies on strain cld-2 [2, 5, 12]. Growth in the presence of 2-MP led to two novel major peaks in the chromatograph with retention times of 2.61 and 3.24 min (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Sun and O'Riordan [11] showed that BCFA-deficient mutants grew and survived less well in macrophages, exhibited decreased production of the key virulence factor listeriolysin O, and were highly attenuated in a murine model of infection. In an extension of these studies, BCFAs played a critical role in protection against antimicrobial peptides and peptidoglycan hydrolases [12]. In all these cases 2-MB restored the anteiso C15:0 and anteiso C17:0 fatty acid content and the defects in the mutants to a large extent.…”
Section: Introductionmentioning
confidence: 99%
“…As examples, Salmonella enterica senses its levels of ATP to control a virulence locus (98), while Listeria monocytogenes and Legionella pneumophila regulate virulence factor production in response to metabolites such as fatty acids and amino acids (99)(100)(101). The demonstrated effects of various metabolic activities in B. burgdorferi and other pathogens indicate that previously reported effects of temperature on other bacteria should be reexamined to determine the actual regulatory cue(s) (30).…”
Section: Discussionmentioning
confidence: 99%
“…monocytogenes, where BCFAs comprise 75 to 98% of the membrane (13, 14, 16, 21, 142). BCFA-deficient strains have increased susceptibility to antimicrobial peptide killing and lysozyme digestion and decreased production of the virulence factor listeriolysin O (143), all of which likely contribute to the decreased intracellular growth and virulence of a strain deficient of BCFAs (143, 144). In S.…”
Section: Bcaas At the Crossroads Of Metabolism And Virulencementioning
confidence: 99%